2012
DOI: 10.4103/0019-5413.98826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immobilization on thickness of superficial zone of articular cartilage of patella in rats

Abstract: Background:Articular cartilage normally functions as a load-bearing resistant material in joints. Patella is composed of hyaline cartilage and spongy bone. Chondrocytes form only 1–5% volume of the articular cartilage. They receive their nutrition by diffusion through the matrix. The alteration in articular cartilage become apparent following immobilization, from 4 to 6 weeks. Until now, focus of research has been the whole cartilage. Zonal changes have not been studied in detail. Since superficial zone bears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
1
10
0
3
Order By: Relevance
“…Immobilization leads to degeneration of the articular cartilage, with atrophic changes, decreased thickness, decreased synthesis of cartilage matrix proteoglycans, irregular cartilage surface, cartilage necrosis and ulceration, increased number of inflammatory cells, and lower total cartilage mass and volume. ( 7 - 9 , 16 , 19 - 24 ) Some of these characteristics were observed in the group subjected to sham ovariectomy and immobilization, indicating that immobilization may have aggressive effects as early as at 2 weeks. Also, estrogen deficiency causes morphological changes in cartilage, leading to its degeneration, ( 25 ) and this is supported by the observation of lower cartilage thickness in the left limb only in the ovariectomized group.…”
Section: Discussionmentioning
confidence: 96%
“…Immobilization leads to degeneration of the articular cartilage, with atrophic changes, decreased thickness, decreased synthesis of cartilage matrix proteoglycans, irregular cartilage surface, cartilage necrosis and ulceration, increased number of inflammatory cells, and lower total cartilage mass and volume. ( 7 - 9 , 16 , 19 - 24 ) Some of these characteristics were observed in the group subjected to sham ovariectomy and immobilization, indicating that immobilization may have aggressive effects as early as at 2 weeks. Also, estrogen deficiency causes morphological changes in cartilage, leading to its degeneration, ( 25 ) and this is supported by the observation of lower cartilage thickness in the left limb only in the ovariectomized group.…”
Section: Discussionmentioning
confidence: 96%
“…Besides basic bright-field illumination [36,60], enhanced contrast methods such as dark-field illumination, phase-contrast and differential interference contrast techniques have been applied [61][62][63][64]. White light microscopy is primarily used for routine analysis (monitoring cell number and morphology after seeding of scaffolds) and for imaging stained tissue slices (histology [65]; various stains such as H&E, Von Kossa, trichrome, alcian blue and others are available [39,50,[66][67][68][69][70][71]). A typical study that makes use of histology was carried out by Gerhardt et al [40], who investigated scaffolds after explanation to observe their degradation, cellular infiltration and vascularization (figure 2a).…”
Section: Transillumination and Fluorescence Microscopymentioning
confidence: 99%
“…The impact of immobilisation and unloading of joints on articular cartilage has been investigated in animal models [2,11] and humans [12,27,28]. Previous studies have demonstrated that joint immobilisation and unloading lead to functional adaptation of articular cartilage that involve morphologic changes of chondrocytes and cartilage matrix [13,15]. Articular cartilage changes were detected as early as one week following immobilisation of rat knee joint [2,3].…”
Section: Introductionmentioning
confidence: 99%